2014
DOI: 10.1021/ol502738a
|View full text |Cite
|
Sign up to set email alerts
|

A Free-Radical Cascade Methylation/Cyclization of N-Arylacrylamides and Isocyanides with Dicumyl Peroxide

Abstract: A free-radical cascade methylation/cyclization of a wide range of N-arylacrylamides and isocyanides is demonstrated by using dicumyl peroxide as the methylating reagent, which provides a convenient and selective access to various methylated N-heterocycles such as oxindoles and phenanthridines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(30 citation statements)
references
References 51 publications
(20 reference statements)
0
30
0
Order By: Relevance
“…Based on these observations and literature reports, we propose a plausible catalytic cycle (Scheme ). The first step involves a copper‐assisted homolysis of DCP to generate a cumyloxyl radical . Thereafter, the selective hydrogen atom abstraction from acetophenone 2 a by the cumyloxyl radical generates the corresponding radical intermediate A , followed by its addition to the C=C bond of N ‐acrylamide 1 a , affording radical intermediate B .…”
Section: Methodsmentioning
confidence: 99%
“…Based on these observations and literature reports, we propose a plausible catalytic cycle (Scheme ). The first step involves a copper‐assisted homolysis of DCP to generate a cumyloxyl radical . Thereafter, the selective hydrogen atom abstraction from acetophenone 2 a by the cumyloxyl radical generates the corresponding radical intermediate A , followed by its addition to the C=C bond of N ‐acrylamide 1 a , affording radical intermediate B .…”
Section: Methodsmentioning
confidence: 99%
“…An elevated temperature cound not give a better yield. Next an array of metal and or metal salts were screened (entries [7][8][9][10][11][12][13][14]. As a result, low yields of the products were obtained with or not the catalysts (entry 15).…”
mentioning
confidence: 99%
“…[10][11][12] However,d irectC ÀH methylations by using cobalt catalysis have been very rare and have been achieved only on two isolated substrates, N-methyl-1-naphthamide [9f] and benzo[h]quinoline [9g] with MeMgBra s the methyl source under oxidative conditions. In this paper,we would like to report the cobalt(II)-catalyzed direct CÀHm ethyl-ation of unactivated (hetero)arenes by using dicumyl peroxide (DCP) [13] as both the methyl source and hydrogen acceptor, and 2-pyridinyl isopropyl (PIP) [14] as ab identate directing auxiliary (Scheme 1B).…”
mentioning
confidence: 99%
“…[Co(acac) 3 ]p roduced the desired product in moderate yield (entry 10), suggesting that the reaction may be initiated by acobalt(III) species. Severalother peroxides were investigated in this reaction (entries [11][12][13], and it was found that dicumyl peroxide (DCP) provided the best result with an 88 % yield of 2a.T he product 2a was formed in 80 %y ield when 5mol %[ Co(acac) 2 ]w as used in this reaction (entry 14), andn o product waso bserved in the absence of ac obalt catalyst (entry 15).…”
mentioning
confidence: 99%
See 1 more Smart Citation